Subsidization and Structural Change in Eastern German Transition: Did Economic Policy Meet Its Objectives? - Katja Gerling (Kiel Institute of World Economics (IfW), 2000)
Economic policy interventions of a scale as effected in eastern Germany can be expected to have a significant impact on the economy, which may be in accordance with the objectives of the policy measures or manifest itself in distortions of several kinds. This paper analyzes the structural effects of investment subsidization as one of the core policy instruments by means of an error-correction model of factor demand and output. It intends to find out whether investment subsidization contributes to creating competitive economic structures, employment and growth or whether it just fosters an exaggerated capital intensity.
Keywords: C51; C33; H20; E24; E23; E22; 330; Subsidization; transition; factor demand; substitution; panel estimation; Investitionspolitik; Wirtschaftspolitische Wirkungsanalyse; Faktornachfrage; Faktorsubstitution; Kapitalintensität; Schätzung; Wirtschaftliche Anpassung; Beschäftigungseffekt; Produktivität; Neue Bundesländer